Cavitation resistance of vacuum-arc coverings deposited on substrate of different orientation - Маринин, Владимир Григорьевич; Коваленко, Владимир Иванович (Technology audit and production reserves, 2013)
Here we set forth the results of measuring the cavitation resistance of coverings, rigidly fixed abrasive particles of vacuum-arc coverings, obtained from the erosion plasma of titanic and zirconium cathodes on the substrates with different orientation of their surfaces relative to the surfaces of cathodes. The cavitation area was developed under the end surface of the radiator of the exponential profile, connected to the ultrasonic wave generator. The oscillation amplitude of the concentrator end surface makes up 30±2 micrometers, the oscillation frequency amounts to 20 kilohertz. The erosion of the samples was measured by means of the gravimetric method. The weight loss measurement accuracy is ± 0,015 mg. The experimental data was used to build kinetic curves of material destruction of the samples. The abrasive wear was measured in accordance with the plane–disc scheme. The coverings were tested by laying them on the plane surface, while the disc was made of materials with rigidly fixed abrasive particles. The rotation speed of the disc surface, contacting with a covering, is 4,38 m/s, and the sample load against the covering equates to 2,2 H. The mass losses of the covering within a certain interim were measured as well. The micro hardness of the samples was measured with the help of the Micro Hardness Tester - 3. The research results have shown, that the cavitation resistance, micro hardness, abrasive resistance of titanic, zirconium and Ti – Zr system coverings, depend nonlinearly on the value of the angle between the substrate and the cathode surface. The formation of the Ti – Zr system coverings ensures the expansion of the area with identical covering properties. The area gets smaller by augmenting the vacuum chamber pressure.